THE EFFECT OF TECHNOLOGY, FACILITIES, AND READING COMPREHENSION ON STUDENTS INTEREST IN READING INTERNATIONAL JOURNAL AT BINA INSAN UNIVERSITY LUBUKLINGGAU - Riance, Astri (Universitas Muhammadiyah Palembang, 2021)
The problem in this research was about the low reading international journal interest of students at Bina Insan Lubuklinggau. This research was a quantitative study by using SPSS program in processing the data . The data collection techniques used were questionnaires, observations, and documents. The population were all of the students at Bina Insan University Lubuklinggau with the total sample was 33 students using the accidental sampling technique. The results showed that technology (X1) had a significant effect on students interest in reading International Journal (Y) because t count (12.685)> t table (1.699), facilities (X2) had a significant effect on students interest in reading International Journal (Y) because t count (2.884)> t table (1.699) ), and reading comprehension (X3) has a significant effect on students interest in reading International Journal (Y) because t count (2.477)> t table (1.699). And technology (X1), facilities (X2), and reading comprehension (X3) have a significant effect on students interest in reading International Journal (Y) because F count (52.161)> F table (3.39). So it can be concluded that there was a significant influence between technology, facilities, and reading comprehension on students interest in reading International Journal at Bina Insan University Lubuklinggau